2018
DOI: 10.2147/idr.s185511
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a 14-day quadruple-therapy regimen for third-line <em>Helicobacter pylori</em> eradication

Abstract: PurposeTo assess the efficacy of amoxicillin, tetracycline, high-dose metronidazole, and a proton-pump inhibitor for third-line Helicobacter pylori eradication.MethodsWe enrolled 70 consecutive patients who had registered, failed to respond to two rounds of H. pylori eradication, and undergone endoscopy for H. pylori culture. Seven patients were lost to follow-up. Patients were treated according to the results of antibiotic-susceptibility testing reports (cultured group, n=39). Those who failed the H. pylori c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 36 publications
1
21
0
1
Order By: Relevance
“…Vonoprazan-based regimens may play an important role in second-line H. pylori eradication therapy in the future. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Vonoprazan-based regimens may play an important role in second-line H. pylori eradication therapy in the future. 36 …”
Section: Discussionmentioning
confidence: 99%
“…We have just performed (in 2020) an updated meta-analysis comparing empirical versus susceptibility-guided treatment of H. pylori , 59 including 40 studies. 60100 When only assessing first-line treatments, better efficacy results were obtained, overall, with the susceptibility-guided strategy (although the results were borderline statistically significant). However, when considering only empirical up-to-date first-line quadruple regimens (that is excluding the suboptimal triple therapies) no differences in efficacy were found versus the susceptibility-guided group.…”
Section: What Is the Comparative Effectiveness Of Susceptibility-guided Versus Empirical Strategy For First-line Treatment?mentioning
confidence: 97%
“…57 In our updated meta-analysis, only two studies including at least third-line rescue regimens were identified, and similar efficacy results were found between both tailored and empirical strategies. 86,88 The aim of a recent systematic review was to evaluate the effectiveness of susceptibility-guided therapy as third-line therapy (without comparing it with empirical treatment). 102 Four observational studies were included (no comparative studies were found), and the pooled mean eradication rate with susceptibility-guided therapy was only 72%.…”
Section: Susceptibility-based Strategy and Test-andtreat Strategy: A mentioning
confidence: 99%
“…15 Hybrid therapy has been proposed as a means of combining the benefits of the sequential and concomitant regimes but has been criticized as over-complicated and hence compromising on adherence to therapy. 18 Regarding the sequential therapy, which was proposed as a means of overcoming antibiotic resistance, an interesting study from Italy where H pylori primary resistance to antimicrobials tested is high showed eradication rates for 10-day sequential therapy of 97% in strains susceptible to clarithromycin and metronidazole, 96% in strains resistant to metronidazole, 93% in strains resistant to clarithromycin, and surprisingly even 83% in strains resistant to both clarithromycin and metronidazole. A randomized controlled trial of 352 patients in Taiwan found 96% eradication rates for both reverse hybrid and bismuth-based quadruple therapy.…”
Section: Quadruple Con Comitant S Equential and Hyb Rid Ther Amentioning
confidence: 99%
“…17 As a rescue therapy for third line in a highly resistant set of cases (79% resistant to clarithromycin, 95% to levofloxacin, and 67% to metronidazole), eradication rates of only 52% were seen for 14-day quadruple therapy, compared to 81% for susceptibilityguided treatment. 18 Regarding the sequential therapy, which was proposed as a means of overcoming antibiotic resistance, an interesting study from Italy where H pylori primary resistance to antimicrobials tested is high showed eradication rates for 10-day sequential therapy of 97% in strains susceptible to clarithromycin and metronidazole, 96% in strains resistant to metronidazole, 93% in strains resistant to clarithromycin, and surprisingly even 83% in strains resistant to both clarithromycin and metronidazole. 19…”
Section: Quadruple Con Comitant S Equential and Hyb Rid Ther Amentioning
confidence: 99%